NATURAL LAW, NATURAL REASON, AND THE ORIGINAL COMPACT IN ALGERNON SIDNEY - Paniagua Vega, Esteban (2026)
This article systematizes a portion of a broader research project previously conducted by the author. It examines, using a contextualist approach, some of Algernon Sidney's main arguments regarding natural law, natural reason, and the original compact. The aim is to demonstrate that other authors addressed these topics in the 1680s and that they were neither exclusive to nor original to John Locke, the author whom Western political theory has canonized as the father of liberalism. Sidney's arguments are presented in light of his opposition to the Anglican Church and, above all, to Charles II's ambitions to rule as an absolute monarchy in England.